21st Century Skills/4C Skills’ Integration in English Teaching Documents Used in EFL Classroom - Marwa; Herlinawati Herlinawati; Herdi Herdi (Universitas Lancang Kuning, 2023)
This content analysis research highlights 21st-Century/4Cs skills that characterize the quality of teaching materials integrated to culture in higher education institutions. This research was grounded from teaching documents obtained from the English lecturers, Faculty of Education and Vocational Studies (FADIKSI), Universitas Lancang Kuning, Indonesia from February until July, 2022. The research context was based on teaching documents (teaching syllabus and semester tests) with 4C skills’ integration. There were 16 collected teaching documents consisting of 8 teaching syllabus and 8 semester tests. The checklist of 21st-Century Skills/4Cs rubric covers “Communication”, “Creativity”, “Critical Thinking”, and “Collaboration” was adapted from the CTE Career Ready Practices. This research reveals the integration of 4Cs skills analyzed from teachers’ teaching syllabus and semester tests documents reached the levels of “Meet Competency” and “Approaching competency” levels. This portrait represents teachers’ adequate understanding of 21st-Century skills/4Cs skills. The further research recommends teachers provide and develop classroom environments of 21st-Century skills integrated to culture in the area of teacher professional development.